Opportunities of Using Nanocellulose in Construction Materials - Murtada Alrubaie; Sa'ad Fahad Resan (BioResources, 2023)
Numerous efforts have been made to mitigate the negative impacts of the production of construction materials on the environment. A reduction in the usage of virgin raw materials and the utilization of the waste materials or the biobased materials are examples of these efforts. However, a potential threat to the environment persists. Bacterial nanocellulose shows promise as a further way to produce environment-friendly construction materials.